CONFIDENCE AND DOUBT JUVENILE MUSLIM LIFE-WORLDS, RELIGIOUS ORIENTATION, ISLAMIC THEOLOGY AND EDUCATION IN GERMANY - Harry Harun Behr (Analisa: Journal of Social Science and Religion, 2018)
The article is based on first findings of interdisciplinary research that is still in progress. It has to be understood as the science-based counter-speech against increasing anti-Muslim racism. Young Muslims are under surveillance of public and media attention in Germany. Islam is being debated in terms of regal and security politics and less within the signature of religion in terms of spirituality, aesthetics, life-world orientation, ethics, morale and religious life-styles. Hence, they are being transformed into a kind of ethnic tribe that needs special treatment. This comes along with the impending deployment of religious freedom as it is guaranteed by the German constitution. Especially right-wing nationalist and folkish consent has it that Muslims serve as a reason for redesigning religious politics in Germany that drifts away from the standards of human rights. The research findings presented here focus on juvenile Muslims as humans, pupils and citizens instead. It aims at a better understanding of their psychological and social framing. This plays an important role with regard to schooling in general and Islamic religious education in special. The findings are based upon the qualitative analysis of semi-structured interviews. This contribution also takes theological and anthropological aspects into account. In the end preliminary recommendations for changes in the educational setting are given.